Habitat space and energy availability as determinants of size distributions of lotic assemblages - Lento, Jennifer (University of Ottawa (Canada), 2010)
Size spectra in aquatic systems have shown a strong consistency of shape across a range of environmental conditions and among different groups of organisms, with higher normalized biomass of small organisms than large. Two main hypotheses have been proposed to explain this consistency in patterns. The energy hypothesis states that because of the inefficient transfer of energy between trophic levels, large organisms (as predators) have less energy available to them per unit habitat than small organisms. The habitat hypothesis states that space availability in the habitat shapes size spectra because small organisms perceive greater habitat space due to the presence of crevices and interstitial spaces that large organisms cannot access. My research examined body size spectra of organisms in 17 stream sites, testing both the energetic and habitat hypotheses for macroinvertebrates, crayfish, and fish. Body size research in lotic systems has rarely included all three groups of organisms, despite the potential importance of large organisms to ecosystem function. I developed a sampling method (electrobugging) to improve collection of large mobile macroinvertebrates; this method collected additional taxa and size classes not sampled by traditional methods. Slopes of size spectra including macroinvertebrates, crayfish, and fish were similar among sites. Large macroinvertebrates, crayfish, and fish contributed approximately half or more of the biomass in each site, while the contribution of small macroinvertebrates was negligible. To examine the habitat hypothesis, I developed a method to estimate habitat space from digital photographs of stream substrates by fitting organisms of different sizes to profiles extracted from the photos. Stable nitrogen isotopes were used to estimate trophic position and test the energetic hypothesis. The results of the test of both hypotheses suggested that both energy availability and space availability affected the normalized biomass of organisms in our study sites, although energy availability explained more of the variation in normalized biomass. The strong relationship between normalized biomass and delta15N suggested that energy availability contributed to primary structuring of size spectra, controlling the negative linear relationship of normalized biomass with size. Space availability had a weaker effect on normalized biomass, and may have contributed to secondary structuring of size spectra, controlling deviations from linearity in the normalized biomass-body size relationship.
Keywords: Biology, Ecology.